Outcome-based education : comparing students' perceived learning outcomes with their assessment scores / Thevy Rajaretnam and Bhajan Kaur - Rajaretnam, Thevy; Kaur, Bhajan (Research Management Institute (RMI), 2012)
The purpose of this study was to ascertain whether the perception of the 30 undergraduates in the Faculty of Dentistry who underwent the Language Enhancement for the Health Sciences course regarding their mastery of the learning outcomes was reflected in their assessment scores as a result of the teaching learning process using the a BE & SCL curriculum. These students learnt skills broadly underfour course outcomes which were further subdivided into 24 learning outcomes. The four course outcomes were assessed through four on-going formative assessments. Students responded to a Course Entrance Survey and a Course Exit Survey. Their responses to both these surveys were analysed using the paired samples t-test to find out the differences in their perception of their mastery of the learning outcomes. The differences in their perception were compared to their performances in the assessments using the Pearson correlation analysis. Although there was a significant difference in the students' perception of their mastery of the learning outcomes, it was not reflected in their performances in the assessments.